2017
DOI: 10.1021/acs.energyfuels.7b01312
|View full text |Cite
|
Sign up to set email alerts
|

Deposit Shedding in Biomass-Fired Boilers: Shear Adhesion Strength Measurements

Abstract: Ash deposition on boiler surfaces is a major problem encountered during biomass combustion. Ash deposition adversely influences the boiler efficiency, may corrode heat transfer surfaces, and may even completely block flue gas channels in severe cases, causing expensive unscheduled boiler shutdowns. Therefore, timely removal of ash deposits is essential for optimal boiler operation. In order to improve the understanding of deposit shedding in boilers, this study investigates the shear adhesion strength of bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 54 publications
(123 reference statements)
5
33
0
Order By: Relevance
“…A video of deposit formation and shedding on the steel tube can be found in the supplemental material (Video S1), or accessed at youtu.be/gLSHd8fAZo0. The results concur with previous investigations [12,23], establishing debonding as the dominant mechanism of deposit shedding in boilers.…”
Section: Effect Of Probe Residence Timesupporting
confidence: 92%
See 2 more Smart Citations
“…A video of deposit formation and shedding on the steel tube can be found in the supplemental material (Video S1), or accessed at youtu.be/gLSHd8fAZo0. The results concur with previous investigations [12,23], establishing debonding as the dominant mechanism of deposit shedding in boilers.…”
Section: Effect Of Probe Residence Timesupporting
confidence: 92%
“…Visual observations of the formed deposits (see The experimental results agree with full-scale investigations [9], where increasing flue gas temperatures led to increased deposit formation. Furthermore, it was observed that increasing the flue gas temperature in the experiments resulted in increased adhesion strength of the deposits to the steel tube, as indicated by previous studies [23]. Deposit shedding was not observed in any of the reported experiments.…”
Section: Effect Of Flue Gas Temperaturesupporting
confidence: 73%
See 1 more Smart Citation
“…1,2 Combustion of biomass in suspension-fired boilers can produce renewable, CO 2 -neutral electricity with a higher electrical efficiency compared with that of grate-fired boilers. 3 However, during the combustion process of biomass, significant amounts of Kspecies, such as KOH, KCl and K 2 SO 4 , are released to gas phase in the boiler chamber, and this leads to deposit formation, corrosion [4][5][6][7][8][9][10][11][12] as well as de-activation of SCR (Selective Catalytic Reduction) catalysts. [13][14][15][16][17][18] Ash deposition and corrosion problems may be mitigated by reducing the super heater temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass suspension-combustion has a higher electrical efficiency and higher load-flexibility compared to traditional grate-fired boilers, but the ash-related problems, including deposition, corrosion and SCR catalyst deactivation, may be more severe [1] than that in grate-fired boilers [2][3][4][5][6][7][8][9][10], due to a higher concentration of fly ash in the flue gas [6]. Potassium originating from biomass is the primary cause for the ash-related problems.…”
Section: Introductionmentioning
confidence: 99%